Accounting Information in Financial Contracting: The Incomplete Contract Theory Perspective - CHRISTENSEN, HANS B.; NIKOLAEV, VALERI V.; WITTENBERG‐MOERMAN, REGINA (Journal of Accounting Research, 2016)
ABSTRACT This paper reviews theoretical and empirical work on financial contracting that is relevant to accounting researchers. Its primary objective is to discuss how the use of accounting information in contracts enhances contracting efficiency and to suggest avenues for future research. We argue that incomplete contract theory broadens our understanding of both the role accounting information plays in contracting and the mechanisms through which efficiency gains are achieved. By discussing its rich theoretical implications, we expect incomplete contract theory to prove useful in motivating future research and in offering directions to advance our knowledge of how accounting information affects contract efficiency.